Rational Design of Packaging: Toward Safer and Ecodesigned Food Packaging Systems - Zhu, Yan; Guillemat, Bruno; Vitrac, Olivier (Frontiers in Chemistry, 2019)
It is necessary and urgent to reduce the impact of single-use plastics and in particular those used for beverages and similar products. Fewer plastics or reduced shelf-life need to be explored simultaneously while keeping open the possibilities of bringing on the innovative market designs and consumer experiences. This work details a general computational framework bridging simulation of coupled mass transfer and non-linear thermodynamics with 3D geometry optimization, ecodesign and other mass transfer-related risks (collapse, migration of chemicals). The three-dimensions (impacts, design, shelf-life) of the storage of alcoholic beverages in plastic containers are presented as a representative case-study of the multi-objective ecodesign problem and as an illustration of new trends to accelerate prototyping and innovation. The capacity to evaluate, maximize product shelf-life and minimize packaging waste was tested on 450 miniatures served usually in plane and train. Four alcoholic strengths (including pure water) and four storage conditions were considered. Several alternatives (900 different 3D designs) were explored by simulation and constrained optimization to reach the targeted shelf-life. The large set was used to establish the Pareto optimal design enabling to minimize weights while maximizing shelf-life. The approach is sufficiently versatile and flexible to adapt arbitrary designs and additional phenomena controlling shelf-life (aroma scalping, oxidation, migration of non-intentionally added substances).